Generator zestawień danych liczbowych - Swacha, Jakub; Budzowski, Roman; Kulpa, Artur (Generator of Numeric Data Lists, 2006)
The paper describes an algorithm for automatic generating numeric data lists based on a natural language text. The numeric data lists generated by the described algorithm consist of document sentences containing essentially relevant numbers. The sentence selecting algorithm is based on heuristics. Its usefulness has been verified by its software implementation and running tests on a sample text corpus. The automatically produced numeric data lists may be used as document digests (thus being useful for authors, editors, and readers), and also in applications like information retrieval and extraction as a search-supporting tool, especially when the user has not specified the correct search keyword.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 152-159